Energy Efficient Routing Protocol for Secure Wireless Sensor Network - Kumar, R; Tripathi, S; Agrawal, R (International Journal of Computer Sciences and Engineering, 2025)
WSN (Wireless Sensor Network) has proved to be a boon for data collection from hard to reach places which were otherwise beyond the physical constraint of humans. WSN has found its way into key fields such as Environment monitoring, transportation, security, military, catastrophic area and medical industry. WSN strives on limited power consumption, as charging the battery in some circumstances is not a practical solution and so energy consumption of WSN has to be looked after and for energy efficient communication in WSN, a series of routing techniques has been adopted, the most effective being LEACHES. Simulation results shows a decrease in energy consumption when distance between the cluster heads is reduced.